Elevated physiological plasticity in xerophytic-deciduous shrubs as demonstrated in their variable maximum carboxylation rate. (November 2022) - Xu, Mingze; Zha, Tianshan; Tian, Yun; Liu, Peng; Jia, Xin; Bourque, Charles P.-A.; Jin, Chuan; Wei, Xiaoshuai; Zhao, Hongxian; Guo, Zifan
Highlights: The V cmax of Artemisia ordosica has high seasonal and interannual variation. Seasonal V cmax - N area relationship is sensitive to soil water content(VWC). Interannual variation in V cmax is regulated by annual mean VWC. Abstract: A plant's photosynthetic capacity is typically reflected by its maximum carboxylation rate ( V cmax ), which varies with time and plant functional type. In what way V cmax in a xerophytic-shrub species changes in response to variation in its desert habitat remains poorly understood. In this study, V cmax was continuously monitored in a common desert-shrub species, Artemisia ordosica, with a portable photosynthetic system over seven growing seasons from 2013 to 2019. V cmax 's annual and interannual variations were subsequently assessed in conjunction with a meta-analysis carried out as a separate study. V cmax in the species did not show a distinct seasonal pattern over the seven growing seasons. It rather displayed extensive year-to-year variations in the seasonal peak and its associated timing, exhibiting greater plasticity as compared with other plant functional types. Seasonal variation in V cmax was primarily controlled by leaf nitrogen content per area ( N area ) in a positive, linear manner, with the relationship's sensitivity varying as a function of soil volumetric water content (VWC). Interannual variation in V cmax was regulated by annual mean VWC, also in a positive, linear manner. The effect of N area on V cmax was amplified during the leaf-expanding stage of the shrub. Given severe drought anticipated under continued climate change, xerophytic shrubs are believed sufficiently malleable to acclimatize to ongoing environmental change in deserts.